The Effect of Range of Motion Exercise to Improve Muscle Strength on Physical Mobility Barriers in Osteoarthritis Patient - Ulif Ihwansyah; Prasanti Adriani; Dwi Puji Putranti (Genius Journal, 2022)
Objective: To determine the effect of ROM activity therapy to increase muscle strength on physical mobility barriers in osteoarthritis cases. Methods: This case study uses descriptive methods to describe assessment, data analysis, nursing plans, interventions, implementation, evaluation by describing cases and using a nursing process approach so that it focuses on one of the important problems of osteoarthritis. Assessment is done by history taking and observation. Nursing diagnoses are determined by NANDA, while nursing plans are adjusted to interventions in the Nursing Intervention Classification (NIC), implementation is carried out according to nursing care plans that have been prepared, and nursing evaluations are documented using the SOAP model. Results: The results of the evaluation were carried out within a period of 3 days, the intervention given with range of motion activity therapy had an effect in increasing lower extremity muscle strength. The patient cannot move freely and has difficulty carrying out activities, for that the authors design an intervention especially to increase muscle strength and after implementation the patient can perform optimal movements. Conclusion: It was concluded that the effect of ROM activity therapy to increase muscle strength on physical mobility barriers in cases of osteoarthritis. It can be seen from the results of the research evaluation that range of motion exercises before and after can have a major influence in increasing muscle strength.